Analysis of Students' Learning Motivation and Scientific Literacy as a Preliminary Study For The Development of Pacu Jalur Tradition-Based Physics Learning at Sman 1 Logas Tanah Darat - Mugi Sukmawati; Zulirfan Zulirfan; Yennita Yennita (Journal of Educational Sciences, 2026)
Indonesia's low achievement in PISA 2022 scientific literacy, ranking 68th globally with a score of 398 points, reflects systemic problems in science education, including physics at the high school level. This study aims to analyze learning motivation and scientific literacy of students at SMAN 1 Logas Tanah Darat as a foundation for developing physics learning based on Pacu Jalur tradition. Using a quantitative approach with descriptive survey design, the research involved 25 students selected through purposive sampling technique. Data were collected using structured questionnaires with 4-point Likert scale covering five dimensions: physics concept understanding, intrinsic motivation, academic self-confidence, applied scientific literacy, and learning support factors. Results show that although students' collaborative skills are relatively high (80%) and some demonstrate self-directed learning initiatives (68%), significant challenges remain. Only 23% of students can apply physics concepts to daily life, 21% show interest in physics phenomena, and 9% have career orientation in physics . Only 28% of students feel confident with mathematical abilities and 32% are comfortable with physics formula derivation. These findings indicate the need for innovative learning strategies that integrate local culture such as Pacu Jalur tradition with Discovery Learning approach to make physics concepts more concrete, contextual, and meaningful.